The Role of Elementary School Teachers in Integrating Climate Change Education to Support Students’ Literacy and Numeracy in Achieving the Sustainable Development Goals - Gufron Amirullah; Dien Nurmarina Malik; Herwina Bahar; Baharudin; Ika Yatri; Trisni Handayani; Uswatun Hasanah (Jurnal Penelitian Pendidikan IPA, 2026)
This study investigates the role of elementary school teachers in integrating Climate Change Education (CCE) and its contribution to teachers’ perceived support for literacy and numeracy in elementary learning. A quantitative survey was conducted with 100 elementary school teachers using a Likert-scale questionnaire measuring teacher role, CCE integration, literacy support, and numeracy support. The instrument demonstrated adequate validity (r-count = 0.48–0.67 > r-table = 0.195) and reliability (Cronbach’s alpha = 0.79–0.86). Descriptive findings indicated relatively high mean scores for teacher role (3.72), CCE integration (3.65), literacy support (3.58), and numeracy support (3.49). Correlation analysis showed positive relationships between teacher role and CCE integration (r = 0.68), literacy support (r = 0.62), and numeracy support (r = 0.55). Regression analysis further revealed that teacher role significantly predicted CCE integration (R² = 0.46; Sig. = 0.000). Teacher role also made significant contributions to perceived literacy support (R² = 0.384; p < 0.001) and perceived numeracy support (R² = 0.303; p < 0.001), indicating a stronger contribution to literacy than numeracy. These findings underscore the strategic role of teachers in embedding CCE into competency-oriented elementary instruction and in fostering literacy and numeracy through environmentally relevant learning contexts.